The Psychological Profiles of Internet, Contact, and Mixed Internet/Contact Sex Offenders. (February 2013) - Elliott, Ian A.; Beech, Anthony R.; Mandeville-Norden, Rebecca
A sample of 526 contact offenders, 459 internet offenders, and 143 mixed contact/internet offenders was compared on a range of self-report psychological measures assessing offense-supportive beliefs, socioaffective functioning, emotional management, and socially desirable responding. A multivariate general linear model found a mixed offender profile that was similar to internet offenders rather than contact offenders. The contact group demonstrated lower victim empathy, a greater level of pro-offending attitudes, an externalized locus of control, more assertiveness, a diminished ability to relate to fictional characters, and greater impulsivity than the internet and mixed offender groups. The mixed offender group demonstrated a higher level of empathic concern than the other two groups. The mixed offender group could also be distinguished from the internet group by increased personal distress and perspective-taking ability. A discriminant function analysis highlighted the key linear factor distinguishing between the groups to be one relating to offense-supportive attitudes and identification with fictional characters. A second factor was related to higher levels of empathic concern and poor self-management. These findings are discussed in the context of the potential pathways between internet and contact sexual offenses.